Pengembangan Ensiklopedia Tokoh Wayang Pandawa Sebagai Bentuk Pelestarian Budaya Bagi Siswa Sekolah Dasar - Andika Gutama; Cicilia Ika Rahayu Nita; Hanna Irfani Fauziah (LPPM STIKI Malang, 2024)
In this modern era, knowledge about Javanese culture in elementary schools is increasingly minimal, especially wayang cultural arts. In introducing wayang culture to elementary school students so that it does not become extinct due to the impact of foreign culture entering Indonesia, causing local culture to fade, especially Pandawa wayang. In each wayang character there are positive values ​​to build the character of elementary school students. This study aims to understand the process, feasibility and practicality of developing an encyclopedia of wayang Pandawa characters as a form of preserving Javanese culture for elementary school students. This development study applies the ADDIE model, including analysis, design, development, implementation and evaluation. The data used in the research are quantitative and qualitative. The feasibility test results obtained the